Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/chd.12700
|View full text |Cite
|
Sign up to set email alerts
|

Can transcatheter PDA closure be performed in neonates ≤1000 grams? The Memphis experience

Abstract: Objective Advancements in transcatheter technology have now made it possible to safely close patent ductus arteriosus (PDA) in extremely low birth weight (ELBW) infants. The objective of this article is to describe our technique for transcatheter PDA closure (TCPC) in ELBW infants. Design The techniques employed are very specific to this population and are drastically different when compared to the procedure performed in patients weighing >5 kg. Setting A multidisciplinary team approach should be taken to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 11 publications
(13 reference statements)
1
53
0
1
Order By: Relevance
“…The 3Fcatheter is positioned in the descending aorta. Sathanandam et al have reported a similar technique using a 4Fr angled glide catheter (Terumo, Japan) and a 0.035 Wholey wire (Medtronic, Minneapolis, MN, USA) to cross the PDA antegradely into the descending aorta (59). Other teams have used 4Fr Swan Ganz catheter instead of catheters described above (43).…”
Section: Description Of the Proceduresmentioning
confidence: 99%
“…The 3Fcatheter is positioned in the descending aorta. Sathanandam et al have reported a similar technique using a 4Fr angled glide catheter (Terumo, Japan) and a 0.035 Wholey wire (Medtronic, Minneapolis, MN, USA) to cross the PDA antegradely into the descending aorta (59). Other teams have used 4Fr Swan Ganz catheter instead of catheters described above (43).…”
Section: Description Of the Proceduresmentioning
confidence: 99%
“…Transcatheter therapy has evolved significantly in the last decade. Emerging technology has paved the way for the use of this therapy in smaller and smaller infants [34,35]. The Amplatzer Piccolo Occluder (Abbott Structural Heart, Plymouth, MN, USA) is a self-expandable, Nitinol mesh device with a central cylindrical waist and low-profile retention discs that are marginally larger than the waist, resulting in a nearly isodiametric device.…”
Section: Role Of Transcatheter Pda Closure In the Futurementioning
confidence: 99%
“…• Arterial access in these small patients is very likely to cause damage leading to limb ischemia and should be avoided [34,38]. Instead, antegrade access through the femoral vein is the method of choice.…”
Section: Role Of Transcatheter Pda Closure In the Futurementioning
confidence: 99%
See 2 more Smart Citations